2004
DOI: 10.1073/pnas.0403042101
|View full text |Cite
|
Sign up to set email alerts
|

Seven in absentia homolog 1A mediates ubiquitination and degradation of group 1 metabotropic glutamate receptors

Abstract: Seven in absentia homolog 1A (Siah1A) is a member of the RING-finger-containing E3 ubiquitin ligases and has been shown to bind to the Siah-interacting domain (SID) at the carboxyl-terminal tails of the long splice forms of group 1 metabotropic glutamate receptors (mGluR1a and mGluR5). We examined the function of Siah1A in ubiquitination and degradation of group 1 mGluRs in heterologously expressing cell lines. Coexpression of Siah1A markedly decreased the SID-containing splice forms of group 1 mGluRs but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 38 publications
1
73
0
Order By: Relevance
“…Both Siah-1a and Siah-2 are expressed widely in embryonic and adult mouse tissues (16), and a recent study using a nonspecific Siah-1a͞b probe demonstrated that pyramidal neurons of the hippocampus as well as Purkinje cells express high levels of Siah-1 mRNAs (17). To determine whether Siah-1a has an expression profile similar to that of Af4, in situ hybridization was carried out on adult brain sections using a riboprobe designed from the 3Ј UTR to avoid crossreactivity with Siah-1b (16).…”
Section: Identification Of Siah-1a and Siah-2 As Af4-binding Partnersmentioning
confidence: 99%
“…Both Siah-1a and Siah-2 are expressed widely in embryonic and adult mouse tissues (16), and a recent study using a nonspecific Siah-1a͞b probe demonstrated that pyramidal neurons of the hippocampus as well as Purkinje cells express high levels of Siah-1 mRNAs (17). To determine whether Siah-1a has an expression profile similar to that of Af4, in situ hybridization was carried out on adult brain sections using a riboprobe designed from the 3Ј UTR to avoid crossreactivity with Siah-1b (16).…”
Section: Identification Of Siah-1a and Siah-2 As Af4-binding Partnersmentioning
confidence: 99%
“…In agreement, both proteins were previously shown to be widely expressed in the brain and to be present at the presynapse (25, 35, 36). In addition, SIAH interacts with and promotes the degradation of different synaptic proteins, including the group 1 metabotropic glutamate receptor and the synaptic vesicle protein synaptophysin (36,37). Moreover, endogenous SIAH was shown to be present and to co-localize with synaptophysin in neuritic processes of neuronally differentiated PC12 cells (37).…”
Section: Discussionmentioning
confidence: 99%
“…Proteasome inhibitors can cause cellular apoptosis in proliferating cancer cells by affecting various short-lived proteins, resulting in inhibition of NF-ĸB activity, increased activity of p53 and Bax proteins, and accumulation of cyclin-dependent kinase inhibitors p27 and p21 [Moriyoshi et al, 2004;Van Waes et al, 2007]. Preclinical studies show that malignant, transformed, and proliferating cells are more susceptible to proteasome inhibition than cells in a resting state Sherr, 1996].…”
Section: Proteasome Inhibitionmentioning
confidence: 99%
“…UPS regulates synaptic functions by controlling levels of pre-synaptic proteins [Speese et al, 2003]. At the post-synaptic levels, the UPS regulates the surface expression and internalization of NMDA-and AMPA-glutamate receptors [Moriyoshi et al, 2004]. It has been implicated that mechanical allodynia and hyperalgesia can be prevented with NMDAreceptor antagonists [Laughlin et al, 1997].…”
Section: Ups In Neuronal Signallingmentioning
confidence: 99%